Heat-treated multi-walled carbon nanotubes-supported (Fe, Co, Ni)-coordinated polyporphyrin: A robust air cathode catalyst for rechargeable zinc-air batteries. (20th October 2020) - Mei, Gaoxia; Cui, Lili; Dou, Zhiyu; He, Xingquan
Abstract: Developing robust dual-function oxygen electrode reaction catalysts is vital toward renewable/rechargeable energy systems but remains challenging. In this work, novel electrocatalytically active hybrid materials comprising Fe0.5 Co0.4 Ni0.1 alloy nanoparticles-embedded N-doped carbon nanotubes, named CNTs@(Fe, Co, Ni)PP-T (where T denotes the pyrolysis temperature employed to prepare them), are developed by pyrolyzing the mixture of hyperbranched tri-metal (Fe, Co, Ni)-coordinated polyporphyrin-encapsulated carboxylic acid-functionalized carbon nanotubes and melamine. The materials are demonstrated to act as effective bifunctional oxygen electrode catalysts. Especially, the one generated at 800 °C, termed as CNTs@(Fe, Co, Ni)PP-800, has larger specific surface area, larger active surface area and better electrical conductivity than other as-obtained contrast materials. Undoubtedly, this material displays superior reactive activity for O2 -associated electrochemical reactions in alkaline media, delivering more positive onset (0.988 V vs . RHE) and half-wave (0.837 V vs . RHE) potentials for the reduction of oxygen and a smaller overpotential (355 mV) at 10 mA cm −2 for the evolution of oxygen than its counterparts. In practical application, the CNTs@(Fe, Co, Ni)PP-800 based zinc-air battery (ZAB) achieves a small initial charge-discharge voltage gap of 0.69 V at 2 mA cm −2 and an outstanding cycling durability in 300 cycles of charge-discharge (in over 50 h), superior to the benchmark Pt/C+RuO2 based ZAB under the identical testing conditions. Graphical abstract: Image, graphical abstract